1982
DOI: 10.1021/ba-1982-0200.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting, Processing, and Cooking Influences on Vitamin C in Foods

Abstract: Vitamin C is considered the most labile of the vitamins in our food supply. Reduced ascorbic acid (RAA), which is the predominant form found in foods of plant origin, can be reversibly oxidized to dehydroascorbic acid (DHA). Further irreversible oxidation of RAA or DHA to diketogulonic acid or other products results in loss of biological activity. Oxidation can occur in the presence of metal catalysts, or plant oxidase enzymes, particularly following cell damage, or as a result of heat during food processing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…Therefore, the antioxidant compounds of these vegetables were stable during heating, but were leached out into the cooking water during boiling. Erdman and Klein (1982) reported that when a large volume of water was used for boiling, a higher content of ASA was found in the cooking water, which emphasizes the importance of using a small volume of water in vegetable cookery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the antioxidant compounds of these vegetables were stable during heating, but were leached out into the cooking water during boiling. Erdman and Klein (1982) reported that when a large volume of water was used for boiling, a higher content of ASA was found in the cooking water, which emphasizes the importance of using a small volume of water in vegetable cookery.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave heating has wellknown advantages over boiling, the conventional heating process, because foods are heated directly and rapidly without contact with hot surfaces (Young & Jolly, 1990). Many experiments have been carried out on the effect of processing and cooking on vitamin C content in vegetables (Erdman & Klein, 1982;Kiribuchi & Kawashima, 1987;Sako et al, 1996;Howard et al, 1999). It is generally believed that these steps result in significant loss of vitamin C. However, the effect of processing and cooking on the radical-scavenging activity of vegetables has not yet been fully approached.…”
mentioning
confidence: 99%
“…15,23,24 Estimates of vitamin C amounts in foods depend on season, transport of the food, shelf time prior to purchase, storage, and cooking practices. For example, supermarket broccoli compared with wholesaler broccoli can lose 33% of its vitamin C, and boiling vegetables can cause 50% to 80% loss.…”
Section: Dietary Availabilitymentioning
confidence: 99%
“…Cooking vegetables with minimal water or in a microwave oven will decrease vitamin C losses. 23,24 As a supplement, ascorbate is available in tablet and powder forms, with a wide dose range. Ascorbate is part of many multivitamin formulations and is in supplements with selected vita- mins, commonly sold as antioxidant supplements.…”
Section: Dietary Availabilitymentioning
confidence: 99%
“…Oxidation also occurs on exposure to halides, such as hypochlorite (Bielski, 1982); due to concerns about the microbiological safety of freshcut produce, many products are washed in a solution of sodium hypochlorite. Ascorbate is oxidized by interaction with enzymes, such as ascorbate oxidase, polyphenol oxidase, cytochrome oxidase and peroxidase (Erdman and Klein, 1982). Cutting damages cells adjacent to the cut, resulting in the mixing of enzymes and substrates that would be compartmentalized in undamaged tissue (Watada et al, 1990).…”
Section: Introductionmentioning
confidence: 99%